ANALISIS LAJU DEGRADASI DAN DEPRESIASI SUMBER DAYA IKAN LAYANG DI PERAIRAN KABUPATEN MUNA SULAWESI TENGGARA - Wa Ode Piliana; Tridoyo Kusumastanto; Diniah Diniah (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
This research aimed to determine degradation and depreciation rates of scads fish resources in the waters of Muna Regency, Southeast Sulawesi Province. The research was conducted using a case study method. Sampling used was purposive sampling method. Data were analyzed using degradation and depreciation rates. Result showed that degradation and depreciation was yet to occur and still on tolerable limits with the averages of 0.19 and 0.17, respectively